2017
DOI: 10.3390/su9071253
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration for Sustainability in the Food Supply Chain: A Multi-Stage Study in Italy

Abstract: Abstract:The objective of this study is twofold. Firstly, to analyze sustainability practices adopted in collaboration, including vertical collaboration i.e., with other actors or stages upstream or downstream in the supply chain, and horizontal collaboration i.e., with actors such as non-governmental organizations (NGOs). Secondly, to identify the sustainability performance expected from sustainability practices implemented in different supply chain stages. The study reports on a set of case studies represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 39 publications
(143 reference statements)
3
88
0
Order By: Relevance
“…Thus, following the arguments of León-Bravo et al [5], larger companies often feel higher external market pressures to demonstrate sustainability as they are closer to the final consumer. In food SCs, large processors adopt practices to support community and consumer education through external collaboration.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 92%
See 3 more Smart Citations
“…Thus, following the arguments of León-Bravo et al [5], larger companies often feel higher external market pressures to demonstrate sustainability as they are closer to the final consumer. In food SCs, large processors adopt practices to support community and consumer education through external collaboration.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 92%
“…For instance, Touboulic and Walker [76] consider that companies often engage different types of suppliers, which involves, for example, the inclusion of small and medium companies in the strategic suppliers' board. The application of collaboration to the agri-food industry has been researched through studies that demonstrate its relevance, which is clear when related to sustainability [5][6][7]. According to Blome et al [73], sustainability collaboration can be observed as a pathway to address sustainability issues.…”
Section: Supply Chain Collaboration For Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the inter-firm collaboration can achieve sustainable growth by building various eco-networks [6]. For example, in a food supply chain, different collaboration forms between actors of upstream and downstream in each stage of supply chain enable the successful implementation of sustainability practices [7]. In particular, collaboration in various functions such as R&D activities, design, marketing and production is at the center of the recent changes for sustainable growth in the IT service industry across the globe.…”
Section: Introductionmentioning
confidence: 99%